Problem-based learning and 21st-century skills: Are they compatible? - Ni Komang Arie Suwastini; Ni Wayan Nilam Puspawati; Ni Luh Putu Sri Adnyani; Gede Rasben Dantes; Zulidyana Dwi Rusnalasari (EduLite: Journal of English Education, Literature and Culture, 2021)
Rapid changes in the 21st century require students to have not only theoretical knowledge but also high order thinking skills and communicative skills. Arguing that problem-based learning can be a good alternative for improving 21st-century skills, the present study will elaborate on the characteristics, syntax, strengths, and challenges faced in implementing problem-based learning in the classroom. Library research was employed to choose the references for supporting the arguments. Relevant articles were chosen from reputable international journals through Google Scholar, limiting the publication's date from 2015 – 2020, with keywords related to problem-based learning and developing 21st -Century skills. The results reveal that the problems proposed in problem-based learning must be real-life-based and require problem-solving skills. The syntax of the implementation can be adjusted based on the needs of teachers and students. Although problem-based learning might be intricate, suitable strategies can be employed to obtain maximum benefits from this approach. In short, problem-based learning is an appropriate teaching approach to be implemented to meet the needs of the 21st century.